1997
DOI: 10.1038/bjc.1997.125
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel, ifosfamide and cisplatin with granulocyte colony-stimulating factor or recombinant human interleukin 3 and granulocyte colony-stimulating factor in ovarian cancer: a feasibility study

Abstract: Summary The tolerability and efficacy of four courses of paclitaxel and ifosfamide plus cisplatin every 3 weeks was evaluated in patients with residual or refractory ovarian cancer. Additionally, supportive haematological effects of recombinant human interleukin 3 (rhlL-3) and recombinant human granulocyte colony-stimulating factor (G-CSF) were studied. Paclitaxel starting dose was 135 mg m-2 (day 1), with ifosfamide dose 1.2 g m-2 day-1 (days 2-4) and cisplatin dose 30 mg m-2 day-1 (days 2-4). All 16 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In our patient, when paclitaxel was given at 175 mg/m 2 , the mean values for C max , AUC 0→∞ , and CL T with 3363.0 ng/mL, 12,200 ng·h/mL, and 14 L/h/m 2 , respectively, were comparable with the mean values previously reported for the same dosage and schedule of the drug in patients with nonperturbed excretory function (2,18,19) (Tables 2 and 4).…”
Section: Discussionsupporting
confidence: 89%
“…In our patient, when paclitaxel was given at 175 mg/m 2 , the mean values for C max , AUC 0→∞ , and CL T with 3363.0 ng/mL, 12,200 ng·h/mL, and 14 L/h/m 2 , respectively, were comparable with the mean values previously reported for the same dosage and schedule of the drug in patients with nonperturbed excretory function (2,18,19) (Tables 2 and 4).…”
Section: Discussionsupporting
confidence: 89%
“…In our current study, 21 patients (39.6%) with previous chemotherapy for recurrent disease were included and they showed much a higher incidence of neurotoxicity (68% vs 55%, respectively). According to Veldhuis et al (31) , both paclitaxel‐ and cisplatin‐induced neurotoxicities are cumulative and dose related. Another possible explanation may be the different dose schedule of the regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, ifosfamide was combined with vinblastine and gallium nitrate, 34 whereas in two other studies ifosfamide was combined with cisplatin and paclitaxel. 35,36 Based on these data, we decided to evaluate the activity of a three-drug regimen consisting of ifosfamide, paclitaxel, and cisplatin in previously untreated patients who had suboptimally debulked Stage III or IV EOC. In our current Phase II study, we administered paclitaxel at a dose of 175 mg/m 2 intravenously over a 3-hour period on Day 1, ifosfamide 1500 mg/m 2 intravenously over 1 hour on Days 1-3 (with MESNA uroprotection), and cisplatin 75 mg/m 2 intravenously over 2 hours on Day 2.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, paclitaxel and cisplatin were given at the same doses as in our Phase II trial, whereas ifosfamide was infused at a dose of 5 g/m 2 over 24 hours. Myelotoxicity was the most relevant side effect in the study of Veldhuis et al 35 who used the same drug combination as a second-line treatment for patients with residual or relapsing ovarian carcinoma. Zanetta et al 52 observed Grade 3 or 4 neutropenia in 91% of patients with recurrent or persistent squamous cell cervical cancer treated by paclitaxel, ifosfamide, and cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation